The SSH Open Marketplace: increasing the discoverability of your favourite resources - Laure Barbot; Cristina Grisot; Barbara McGillivray; Maja Dolinar; Magdalena Wnuk; Christian Schuster; Elena Battaner Moro; Stefan Buddenbohm; Boavida, C. P.; Michael Kurzmeier; Cesare Concordia; Klaus Illmayer; et al. (10th Conference of the European Survey Research Association (ESRA 2023), 2023)
The Social Sciences and Humanities Open Marketplace (SSH Open Marketplace) - marketplace.sshopencloud.eu - is a discovery portal which pools and contextualises resources for Social Sciences and Humanities research communities: tools, services, training materials, datasets, publications and workflows. The SSH Open Marketplace showcases solutions and research practices for every step of the research data life cycle. In doing so, it facilitates discoverability and findability of research services and products that are essential to enable sharing and re-use of workflows and methodologies. The SSH Open Marketplace might be regarded as an innovative service. It is, of course, a directory in a classic way, indexing information and allowing researchers to navigate their way to new tools and methods. But it is something new, as well: through the creation and marking of relations between indexed items in a semantically much more meaningful way than the limited textual relatedness of keyword or category classes, it creates contextualization which increases the serendipity in the search of resources. This poster, created by the SSH Open Marketplace Editorial Board members provides an overview of what the service is, what is indexes, how it is managed and how it can be used.